Relationship of Front Line Employees’ Emotional Intelligence to Co-Creation, Satisfaction, and Customer Loyalty in Banking Industry - Shoeib, Masoumeh; Salavati, Shahram (European Journal of Sustainable Development, 2018)
This study evaluates the relationship between front line employees’ emotional intelligence with co-creation and customer loyalty. The population under study consisted of expert and managerial level employees at the Pasargad Bank in Tehran; 323 subjects participated in the data gathering process and responded to the questionnaires of emotional intelligence, co-creation, loyalty, and customer satisfaction. Reliability and validity of the tools were assessed using Cronbach’s alpha coefficient and confirmatory factor analysis. Pearson correlation coefficient, structural equation model, and Amos software were used to analyze the data. The results show that front line employees’ emotional intelligence is associated with co-creation, loyalty, and customer satisfaction. In addition, the results confirm the relationship of co-creation and customer satisfaction to customer loyalty; it also suggests that emotional intelligence has an indirect positive and significant effect on customer loyalty through co-creation and customer satisfaction. Keywords: Emotional intelligence, co-creation, customer satisfaction, customer loyalty.